Managing of ventricular reperfusion tachyarrhythmias - focus on a perfused myocardium - Bernikova, O G; Sedova, K A; Durkina, A V; Azarov, J E (Journal of physiology and pharmacology, 2019)
In this study we tested a hypothesis that reperfusion ventricular tachyarrhythmias can be modified by direct control of repolarization duration in the perfused myocardium during ischemic exposure. After induction of coronary occlusion, three groups of rats were given agencies affecting repolarization duration tetraethylammonium (TEA) 4 mg/kg, n = 9; pinacidil (Pin) 0.3 mg/kg, n = 11, and saline as placebo (control) n = 10. Unipolar electrograms were recorded from ischemic and perfused areas using an array of 64-electrodes to obtain activation times (ATs), repolarization times (RTs), activation-repolarization intervals (ARIs) and dispersion of repolarization (DOR). During ischemia/reperfusion ARIs in perfused area did not change in the control, significantly increased in the TEA and decreased in the Pin group in respect to baseline, whereas ARIs significantly decreased in the ischemic zone in all groups. DOR also significantly increased in all groups at ischemia and reperfusion. The incidence and total arrhythmia score of reperfusion tachyarrhythmias were significantly greater in TEA group compared to Pin and control groups. In multivariate regression analysis, incidence of VT/VFs and total arrhythmia score were associated with ARIs in the perfused area. Thus, the effect on repolarization durations in the perfused area modified the incidence and severity of the reperfusion-induced ventricular tachyarrhythmias.
Keywords: Tachycardia, Ventricular; elektrokardiografie; Rats; akční potenciály; srdeční arytmie; Action Potentials; reperfuzní poškození; Rats, Wistar; mužské pohlaví; Reperfusion Injury; Arrhythmias, Cardiac; krysa rodu Rattus; Electrocardiography; myokard; zvířata; Myocardium; Heart; potkani Wistar; komorová tachykardie; srdce; Male; Animals